2021
DOI: 10.1038/s41598-021-83018-1
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea increases lipolysis and deteriorates glucose homeostasis in patients with type 2 diabetes mellitus

Abstract: Obstructive sleep apnoea (OSA) is associated with type 2 diabetes mellitus (T2DM). However, mechanisms mediating association between these two conditions remain unclear. This study investigated, whether the OSA-associated changes in adipose tissue lipolysis might contribute to impaired glucose homeostasis in patient with T2DM. Thirty-five matched subjects were recruited into three groups: T2DM + severe OSA (T2DM + OSA, n = 11), T2DM with mild/no OSA (T2DM, n = 10) and healthy controls (n = 14). Subcutaneous ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Conversely, type 2 diabetes may increase predisposition to, or accelerate the progression of OSA, possibly through the development of peripheral neuropathy and abnormalities of ventilatory and upper airway neural control [ 7 , 8 ]. The prevalence of OSA in patients with type 2 diabetes ranges from 50 to 80% [ 9 , 10 ]. A cross-sectional study confirmed an association between OSA and type 2 diabetes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, type 2 diabetes may increase predisposition to, or accelerate the progression of OSA, possibly through the development of peripheral neuropathy and abnormalities of ventilatory and upper airway neural control [ 7 , 8 ]. The prevalence of OSA in patients with type 2 diabetes ranges from 50 to 80% [ 9 , 10 ]. A cross-sectional study confirmed an association between OSA and type 2 diabetes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also assumed that about 30% of the subjects could decline participation in the study, as well as 12% of the subjects with incomplete STOP-Bang questionnaires. Taking these data into account, we estimated that at least 529 patients were required in order to have a confidence level of 95% [ 8 , 9 ]. As presented in Figure 1 , 553 answered the STOP-Bang questionnaire, 529 having complete data were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…T2DM and OSA are two conditions that increase their mutual risk [ 2 , 7 ]. It was estimated that in patients with T2DM, OSA has a prevalence of 50–80% [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, type 2 diabetes may increase predisposition to, or accelerate the progression of OSA, possibly through the development of peripheral neuropathy and abnormalities of ventilatory and upper airway neural control [7][8] . The prevalence of OSA in patients with type 2 diabetes ranges from 50-80% [9][10] . A cross-sectional study con rmed an association between OSA and type 2 diabetes [11] .…”
Section: Page 4/19mentioning
confidence: 99%